Symptomatic and Electrodiagnostic Features of Peripheral Neuropathy in Scleroderma. Issue 8 (August 2016) - Paik, Julie J.; Mammen, Andrew L.; Wigley, Fredrick M.; Shah, Ami A.; Hummers, Laura K.; Polydefkis, Michael
Abstract : Objective: To determine the prevalence of peripheral neuropathy in scleroderma. Methods: The prevalence of length‐dependent peripheral neuropathy was rigorously assessed using signs and symptoms of neuropathy derived from the Total Neuropathy Score (TNS), and standardized nerve conduction study (NCS). All subjects underwent TNS and NCS. Those who were symptomatic or had NCS evidence of peripheral neuropathy underwent laboratory evaluation for secondary causes of neuropathy. Results: A total of 130 subjects were approached for participation and 60 enrolled. Of the 60 subjects, 50 (83.3%) were female and 37 (61.7%) were of the limited cutaneous subtype. The mean ± SD age was 55 ± 11.1 years, and mean ± SD disease duration was 15.3 ± 10.1 years. A total of 17 of 60 (28%) had evidence of a peripheral neuropathy as defined by the presence of neuropathic symptoms on the TNS (12 of 60) and/or electrophysiologic evidence of neuropathy (5 subjects with neuropathic symptoms and 5 without neuropathic symptoms). Subjects with neuropathy were more likely to be male (60% versus 40%; P = 0.02), African American (41% versus 4.6%; P = 0.001), have diabetes mellitus (17.7% versus 0%; P = 0.02), have limited cutaneous scleroderma (82.3% versus 53.5%; P = 0.04), and have anti‐U1 RNP antibodies (23.5% versus 0%; P = 0.009) than those without neuropathy. A potential nonscleroderma etiology for the peripheral neuropathy such as diabetes mellitus was found in 82.3% (14 of 17) of subjects with neuropathy. Conclusion: While symptoms or objective evidence of peripheral neuropathy are common among patients with scleroderma, the cause may often be attributed to comorbid nonscleroderma‐related conditions.